KHUTHUWATU TA'LIMIL MUHADATSATI FIE TARQIYATI QUDRATI AT-THALABATI 'ALA AT-TAKALLUMI BI MADRASATI AL-'ALIYATI 'ULUMUL QURAN LANGSA - asrul; sabri, hatta (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to determine the application of muhadasah learning techniques to students at Madrasah Aliyah Ulumul Qur'an, Langsa City, who have various competencies, because some of these students are advanced students from public schools, and from other Islamic boarding schools. This heterogeneity resulted in teachers being more extra in choosing methods and techniques that were more accurate in muhadasah learning. This research is a qualitative descriptive research. Data were collected by observation and interview methods, from research data sources, namely teachers, students and the learning process. The findings from the research results are that the combination of high achieving students and students with medium and low competence can contribute to increasing their competence in muhadasah.